НАВЧАЛЬНИЙ ЕСТРАДНИЙ ОРКЕСТР ЯК ОБ’ЄКТ НАУКОВОГО ПІЗНАННЯ (Педагогіка вищої та середньої школи, 2007)
The important questions of methodological bases of functioning of training pops orchestra are considered. In the article Theauthor approached the problem of teaching and education of students in the pops orchestra guiding by strong scientific knowledge’s.